1985
DOI: 10.1180/claymin.1985.020.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Complementarite des rayons X et de la microscopie electronique pour la determination des diverses phases d'une argile zincifere

Abstract: ResumeLe remplissage des cavités karstiques de la région d'Ain Khamouda (Tunisie Centrale) est partiellement constitué d'une argile blanche. Son étude par diffraction X. ATD et analyse chimique traditionnelle montre qu'il s'agit d'un mélange d'halloysite prédominante et de smectite, renfermant plusieurs pourcents de ZnO. Une étude plus détaillée mettant en oeuvre un diffractométre à détecteur linéaire et à ambiance contrôlée, la microscopie électronique à transmission et la microscopie électronique à transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…3b) is supportive of a desulfidation mechanism (reaction 1), although a sulfur-free reaction of the type (Segnit 1961 (4) sillimanite quartz may have also been responsible for the formation of coexisting gahnite and sillimanite in sulfide-free rocks, such as sillimanite-pod rocks, where minor amounts of gahnite occur in sillimanite crystals. Although the adsorption of zincite on kaolinite has not been recognized in natural settings, Rivière et al (1985) reported a spatial association between aluminous clays and Zn(OH) 2 . Further support for the participation of desulfidation mechanisms involving sphalerite in the formation of zincian spinel in Colorado comes from the mantling of gahnite by sphalerite and the presence of a fine dusting of sphalerite inclusions in gahnite at Cotopaxi (Fig.…”
Section: Zincian-spinel-forming Reactionsmentioning
confidence: 99%
“…3b) is supportive of a desulfidation mechanism (reaction 1), although a sulfur-free reaction of the type (Segnit 1961 (4) sillimanite quartz may have also been responsible for the formation of coexisting gahnite and sillimanite in sulfide-free rocks, such as sillimanite-pod rocks, where minor amounts of gahnite occur in sillimanite crystals. Although the adsorption of zincite on kaolinite has not been recognized in natural settings, Rivière et al (1985) reported a spatial association between aluminous clays and Zn(OH) 2 . Further support for the participation of desulfidation mechanisms involving sphalerite in the formation of zincian spinel in Colorado comes from the mantling of gahnite by sphalerite and the presence of a fine dusting of sphalerite inclusions in gahnite at Cotopaxi (Fig.…”
Section: Zincian-spinel-forming Reactionsmentioning
confidence: 99%
“…Since then, this economically valuable clay mineral has been studied in some detail Steinberg et al, 1985;Dupuis et al, 2003). Rivière et al (1985) and Steinberg et al (1985) also described another Zn-rich smectite in the studied material, namely sauconite. This mineral has not been recovered nor identified in this study.…”
Section: Introductionmentioning
confidence: 86%
“…Segnit proposed that• the ZnO originally was adsorbed on kaolinite but this relationship has not been recognized in natural settings. Riviere et al (1985) reported a spatial association between aluminous clays and Zn-hydroxide. Alternatively, Zn derived from exhalative processes may have subsequently been linked to organic or phosphatic material.…”
Section: Quartz-gahnite Horizonsmentioning
confidence: 99%